2017
DOI: 10.1111/jhn.12484
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported dietetic care post hospital for free‐living patients: a Canadian Malnutrition Task Force Study

Abstract: Background: Transitions out of hospital can influence recovery. Ideally, malnourished patients should be followed by someone with nutrition expertise, specifically a dietitian, post discharge from hospital. Predictors of dietetic care post discharge are currently unknown. The present study aimed to determine the patient factors independently associated with 30-days post hospital discharge dietetic care for free-living patients who transitioned to the community. Methodology: Nine hundred and twenty-two medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…This exploratory analysis found that the most commonly reported nutrition-care activities post-discharge were following information provided in-hospital about food intake/community food related services (44% received info, and 65% followed the information), and use of ONS (26.5%). Only 6.8% of participants reported seeing a dietitian post-discharge, which is consistent with the 11% reported in a previous Canadian study [ 14 ]. Similarly, weight gain, loss, and stability were comparable to other Canadian work [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This exploratory analysis found that the most commonly reported nutrition-care activities post-discharge were following information provided in-hospital about food intake/community food related services (44% received info, and 65% followed the information), and use of ONS (26.5%). Only 6.8% of participants reported seeing a dietitian post-discharge, which is consistent with the 11% reported in a previous Canadian study [ 14 ]. Similarly, weight gain, loss, and stability were comparable to other Canadian work [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…Only 6.8% of participants reported seeing a dietitian post-discharge, which is consistent with the 11% reported in a previous Canadian study [ 14 ]. Similarly, weight gain, loss, and stability were comparable to other Canadian work [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The CMTF also identified that most patients did not improve their nutritional status during hospitalisation, and that half of the patients who remained in hospital > 7 days were identified as malnourished at discharge. Furthermore, 75% of malnourished patients did not receive care from a dietician during their hospital stay, and only 11% received dietetic care post‐discharge .…”
Section: Malnutritionmentioning
confidence: 99%
“…A systematic review conducted in 2012 concluded that transitional care initialised in hospitals could yield positive outcomes in hospitalised adult patients 21. One study showed that dietetic care in hospitals was the most influential predictor of post-hospital care 22. Early and extended nutrition intervention can improve nutrition status and reduce length of hospital stay 23.…”
Section: Introductionmentioning
confidence: 99%